028 Sleep loss disrupts hippocampal memory consolidation via an acetylcholine- and somatostatin interneuron-mediated inhibitory gate. (3rd May 2021) - Delorme, James; Wang, Lijing; Kuhn, Femke; Kodoth, Varna; Ma, Jingqun; Jiang, Sha; Aton, Sara
Abstract: Introduction: Sleep loss profoundly disrupts consolidation of hippocampus-dependent memory. To better characterize effects of learning and sleep loss on the hippocampal circuit, we quantified activity-dependent phosphorylation of ribosomal subunit S6 (pS6) across the dorsal hippocampus of mice. Methods: We first measured pS6 throughout the hippocampus after learning (single trial contextual fear conditioning; CFC), and after subsequent sleep or sleep deprivation (SD). To characterize cell populations with activity affected by SD, we used translating ribosome affinity purification (TRAP)-seq to identify cell type-specific transcripts on pS6 ribosomes after SD vs. sleep. We next used pharmacogenetics to mimic the effects of SD, selectively activating hippocampal Sst+ interneurons or cholinergic inputs to hippocampus from the medial septum (MS) while mice slept in the hours following CFC. We also inhibited these neuronal populations to assess effects on memory consolidation. Results: We find that pS6 in enhanced in the dentate gyrus (DG) following single-trial CFC, but is reduced throughout the hippocampus after brief SD – a manipulation which disrupts contextual fear memory (CFM) consolidation. Cell type-specific enrichment analysis (CSEA) of these transcripts revealed that hippocampal somatostatin-expressing (Sst+) interneurons, and cholinergic and orexinergic inputs to hippocampus, are selectively activated after SD. We used TRAP targeted to hippocampal Sst+ interneurons to identify cellular mechanisms mediating SD-driven Sst+ interneuron activation. . We find that activation of Sst+ interneurons is sufficient to disrupt CFM consolidation, by gating activity in surrounding pyramidal neurons, while inhibition of Sst+ interneurons enhances memory consolidation. Similarly, pharmacogenetic activation of cholinergic input to hippocampus from the MS disrupted CFM. Inhibition of MS cholinergic neurons promoted CFM consolidation and disinhibited neurons in the DG, increasing pS6 expression among DG granule cells. Conclusion: Our data suggest that state-dependent gating of DG activity during SD is mediated by cholinergic input. Together these data provide evidence for an inhibitory gate on hippocampal information processing, which is activated by sleep loss. Support (if any): R01-NS118440 to SJA from NINDS, DP2-MH104119 to SJA from the NIH Director's Office, and a Human Frontiers Science Program Young Investigator Award